Is short-term memory capacity (7±2) really predicted by theta to gamma cycle length ratio? - Malenínská, Kristýna; Rudolfová, Veronika; Šulcová, Kateřina; Koudelka, Vlastimil; Brunovský, Martin; Horáček, Jiří; Nekovářová, Tereza (Behavioural brain research, 2021)
Several studies suggest that EEG parameters, reflecting top-down processes in the brain, may predict cognitive performance, e.g. short-term memory (STM) capacity. According to Lisman and Idiart's model, STM capacity is predicted by theta and gamma EEG waves and their ratio. This model suggests that the more periods of gamma band waves fit into one period of theta band waves, the more information can be stored. We replicated the study by Kaminski et al. (2011), which recorded spontaneous EEG activity and measured verbal STM capacity with a modified digit span task from the Wechsler battery. Our study included more subjects and two EEG recording sessions. We discuss the possible limits of EEG correlates of STM capacity as EEG parameters were not stable across the two measurements and no correlation was found between the theta/gamma ratio and performance in the digit span task.
Keywords: Models, Biological; theta; short-term memory capacity; EEG; biologické modely; gama rytmus EEG; Memory, Short-Term; phase-amplitude coupling; lidé; gamma; Adult; dospělí; Psychomotor Performance; Theta Rhythm; Wechslerovy škály; Female; Male; ženské pohlaví; krátkodobá paměť; theta rytmus EEG; mladý dospělý; Humans; psychomotorický výkon; mužské pohlaví; Young Adult; Gamma Rhythm; cross-frequency coupling; Wechsler Scales